Challenges in achieving more sustainable anaesthesia practices: a narrative review of waste reduction - Erlend J. Skraastad; Ofelia L. Elvir-Lazo; Paul F. White; David Chernobylsky; Ravina Brring; Roya Yumul (BJA Open)
Summary: Anaesthesia and operating room waste contribute to climate change and environmental pollution. Although professional bodies involving anaesthesiologists and surgeons have developed guidelines for supporting environmentally conscious health practices, practitioners face difficulties implementing these protocols in hospitals. This narrative review explores the current literature concerning the environmental impact of anaesthesia and operating room waste. We also discuss obstacles practitioners face in implementing initiatives to decrease anaesthetic and surgical waste. A literature review of peer-reviewed publications was conducted across PubMed, MEDLINE, Google Scholar, and Cochrane Databases to identify relevant articles published from 1980 to 2025. A search of recent anaesthesia, surgery, and medicine journals provided additional data. Around 2% of urban solid waste is medical waste, and healthcare accounts for 5% of global greenhouse gas emissions. Scientific organisations have clearly defined guidelines and recommendations to reduce environmental impact. Barriers to implementing existing recommendations include the lack of proper facilities for recycling waste materials, provider workload concerns, lack of hospital leadership, lack of specific targets and accountability measures, insufficient education, and overall resistance to change. Anaesthetic and solid operating room waste pose significant global health concerns, necessitating a collective effort towards sustainability. Anaesthesia and operating room professionals must recognise their responsibility for promoting environmentally friendly practices. Hospital leadership is pivotal to creating a supportive framework. Hospitals and healthcare systems should be required to adhere to specific targets and accountability measures. Meaningful change requires collaboration with a wide range of stakeholders, including politicians, patients, the medical industry, and scientific organisations.